2023
DOI: 10.1108/bfj-07-2022-0649
|View full text |Cite
|
Sign up to set email alerts
|

Why millennials of smart city are willing to pay premium for toxic-free food products: social media perspective

Abstract: PurposeThis study aims to investigate the smart city millennials’ willingness to pay a premium (WTP) toward toxic-free food products (TFPs). Specifically, it explores the role of social media and environmental concern (EC), using the theory of planned behavior.Design/methodology/approachThe authors used a self-administered questionnaire to gather data from 337 millennials living in an Indian smart city, and analyzed them using PLS-SEM.FindingsThe authors found that both EC and social media influence millennial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 96 publications
0
2
0
6
Order By: Relevance
“…Environmental concern mengacu pada sejauh mana kesadaran masyarakat dalam masalah lingkungan, ikut berkontribusi dalam mendukung menyelesaikannya, dan bersedia untuk memberikan solusi dari permasalahan lingkungan. Sehingga dapat dilihat tingkat kesadaran lingkungan dalam diri konsumen memengaruhi perilaku dan niat beli (Trivedi et al, 2023) . Pembelian suatu produk dapat dipengaruhi oleh kepercayaan, sikap, dan nilai-nilai konsumen dalam lingkungan sosial konsumen (Wiyanti et al, 2023) .…”
Section: Environmental Concernunclassified
See 2 more Smart Citations
“…Environmental concern mengacu pada sejauh mana kesadaran masyarakat dalam masalah lingkungan, ikut berkontribusi dalam mendukung menyelesaikannya, dan bersedia untuk memberikan solusi dari permasalahan lingkungan. Sehingga dapat dilihat tingkat kesadaran lingkungan dalam diri konsumen memengaruhi perilaku dan niat beli (Trivedi et al, 2023) . Pembelian suatu produk dapat dipengaruhi oleh kepercayaan, sikap, dan nilai-nilai konsumen dalam lingkungan sosial konsumen (Wiyanti et al, 2023) .…”
Section: Environmental Concernunclassified
“…Pembelian suatu produk dapat dipengaruhi oleh kepercayaan, sikap, dan nilai-nilai konsumen dalam lingkungan sosial konsumen (Wiyanti et al, 2023) . Pada penelitian terdahulu environmental concern memiliki pengaruh positif terhadap purchase intention (Paramita & Yasa, 2015;Trivedi et al, 2023;Yohana & Suasana, 2020).…”
Section: Environmental Concernunclassified
See 1 more Smart Citation
“…The work of Trivedi et al (2023) has demonstrated that millennial consumers in the smart city of Surat in India were being influenced by social media to pay a premium price for toxic-free food products. In this case, toxic-free food products was a term used to describe all food products which did not contain any additional chemicals, nor were any used in the production process.…”
Section: Being Able To Pay the Premiummentioning
confidence: 99%
“…The work of Trivedi et al. (2023) has demonstrated that millennial consumers in the smart city of Surat in India were being influenced by social media to pay a premium price for toxic-free food products.…”
Section: Being Able To Pay the Premiummentioning
confidence: 99%